An analysis of minority shareholder rights protection between family controlled and non-family controlled Philippine Stock Exchange listed companies - Cruz, Geoffrey Rhoel C. (Animo Repository, 2010)
Issues of corporate governance and financial crisis are no longer new for the Philippines. In fact, the Philippines have endured numerous instances that provided the necessary attention to the concept of corporate governance. Infamous cases of once renowned and market-leader company names such as the College Assurance Plan, Urban Bank and its subsidiary Urbancorp Investment Corp., Victorias Milling Co., Polytechnic Savings Bank, Inc., and BW Resources, were dragged into a mess that led to the collapse of their respective industries. Whether these corporate scandals involve private or publicly listed corporations, depositors and investors were always the losers. Apparently, during such mishaps, the minority investors and shareholders were at the farthest side of the losing end. For countries such as the Philippines where economically dominant family groups often own large corporations, there is a question of how well minority shareholders are protected from corporate decisions that are biased towards controlling shareholders. More often than not, expropriation is reflected through their decisions that prioritize the satisfaction of realistic personal goals rather than the maximization of utility or profit functions. As such, with the limited influence given to minority shareholders in determining company affairs, this study worked on the problem: How protected are minority shareholder rights in family controlled publicly listed corporations? The study likewise assessed whether non-family controlled publicly listed companies in the Philippines better protect minority shareholder rights than family controlled publicly listed companies. Moreover, this work forwarded the hypothesis that minority shareholder rights are poorly protected in family controlled publicly listed corporations into test by analyzing 10 family controlled and non-family controlled corporations. The researched looked into the seven minority shareholder rights identified by the Securities and Exchange Commission (SEC) and the Organization for Economic and Cooperation Development (OECD) (2003, 2004), cited by Abduljaami (2007), Bayless (2008), and the American Bar Association (2003). These were the right to participate, right to ownership, right to dividend, right to inspect corporate books and records and access to information, appraisal right, pre-emptive right, and right to seek corporate redress. However, due to the lack of sufficient data and measures that will effectively quantify the degree of protection provided by family and non-family controlled companies, the study was only able to consider minority shareholder’s right to participation and right to information. In order to measure these two rights, the measurement tools developed by experts and authorities, such as the OECD and the Institute of Corporate Directors (ICD), were utilized. More than that, Stilpon Nestor and Fianna Jesover (2000: 4), Anthony Gonsalvez (2005: 2), and Dr. Cesar G. Saldaña (2010b: n.p.) considered right to participation and right to information as fundamental minority shareholder rights. In general, document reviews were conducted that included 24 data points, with 12 questions representing each minority shareholder rights. The questions were patterned after the iv 2008 Corporate Governance Scorecard for Publicly Listed Companies by ICD, which was also patterned after the OECD Principles of Corporate Governance that was published in 2004. Responses were taken from publicly disclosed documents of companies such as their code of corporate governance, charters, bylaws and other company details that can be obtained from their notices of annual general meetings, annual reports, other SEC filings and website disclosures. Such company information was expected to be publicly disclosed as required by the SEC. Furthermore, the questionnaire also takes on the approach utilized by the ICD that takes the side of an ordinary investor with no special access to any privileged information. The easier for the ordinary investor to get the information, the better it is for minority shareholders. As such, nondisclosure was treated against the company and a demerit on their part. The findings of the study showed that regardless of the equity structure of the company, superior degree of protection was provided to minority shareholder’s right to information as reflected by the mean score of 11.2 for family controlled companies and 10.6 for non-family controlled companies. However, only moderate degree of protection was provided to minority shareholder’s right to participation as indicated by the mean scores of 6.5 for family controlled companies and 5.8 for non-family controlled companies. Apparently, the findings of the study suggest that it is in the area of minority shareholder’s right to participation where significant areas for improvement can be found. The only area for minority shareholder’s right to information that greatly requires improvement is the non-disclosure of director attendance reports on the annual report or information statement. However, for minority shareholder’s right to participation, the factors that substantially influenced the overall moderate protection concerns the following: 1) absence of policies that allow shareholders to remove directors without a cause; 2) non-observance of simple majority voting requirement in approving business combination proposals; 3) absence of policies that provide shareholders the power to call special meetings; 4) non-utilization of written consent in approving company resolutions; 5) minimal significance given to the right of shareholders to submit director nominations for election and other shareholder proposals as typified by the nondisclosure of the due date for such proposals; 6) absence of facilities that support the utilization of proxy voting facilities; and 7) absence of secret voting or confidential voting procedures. The findings of the study also inferred that there were indications that family controlled corporations were more considerate in dealing with minority shareholder rights as shown by the mean scores of 11.2 and 6.5 for family controlled corporations in contrast to the mean scores of 10.6 and 5.8 for non-family controlled companies. The findings likewise suggested that family controlled corporations were more likely to disclose their director attendance report as well as their executive and director compensation policy compared to non-family controlled corporations. There were also indications that family controlled companies were more likely to facilitate proxy voting procedures and observe policies that encourage their shareholders to submit proposals and director nominations for elections. Furthermore, there were also indications that family controlled companies better guarantee shareholders’ ability to remove v directors without a cause, as well as observes simple majority vote requirement for shareholders to amend company bylaws than non-family controlled companies. Despite the lack of significant difference between the levels of protection given to minority shareholder rights by family controlled and non-family controlled corporations, the study would tend to reject the hypothesis that minority shareholder rights are poorly protected in family controlled publicly listed corporation. Instead of the notion that non-family controlled corporations being more protective and better guarantees minority shareholder rights protection, there were indications that point otherwise. In fact in some areas, family controlled companies performed better than non-family controlled companies. However, observations of the study affirmed the findings of the assessment done by World Bank (2006), OECD’s overview of the country’s corporate governance (2007). This evaluation is supported by the Philippine Stock Exchange report on its exposure draft on the PSE corporate governance guidelines (2009) citing Cheung (2009) that corporate governance frameworks and practices in listed companies in the Philippines have improved over a four year period from 2005-2008. Similarly, the findings of another study by the Asian Institute of Management (2009) on corporate governance trends from 2002-2007 concluded that substantial improvements have been noted with publicly listed companies’ compliance to the international disclosure requirements established by the OECD. From 2002 to 2007, more companies have complied with the Securities Regulation Code and Code of Corporate Governance requirement for publicly listed companies to have at least two independent directors or at least 20 percent of the members of the board. These companies have identified independent directors in their annual reports, openly disclosed information regarding related-party transactions, devoted a section of annual reports to a description of their corporate governance practices, and disclosed the adoption of audit, nominating and compensation committee including their charters. Hence, the high recognition of minority shareholders’ right to information is a clear indication that publicly listed companies in the country are continuously adjusting and improving their corporate governance frameworks to suit the present needs of the corporate industry. In effect, it is a work in progress. Moreover, the findings and conclusions of the study do not suggest that such observations alone were enough to provide solid proof that family controlled companies better guarantee minority shareholder rights protection than non-family controlled companies. Instead, the study recognizes that more work remains to be done. In general the study focused on providing an overall assessment of the present state of minority shareholder protection in the country. The research did not intend to provide explanations on why only moderate protection was provided to minority shareholders in the country. Likewise, the study did not intend to provide reasons why there were indications that family controlled companies give a better protection of minority shareholder rights protection than non-family controlled companies. The findings of the study were also constrained by the small sample size it was able to utilize. More than that, due to the difficulties in identifying the exact equity structure vi classification of companies caused by the lack of information that will properly identify the affiliations of the shareholder to the company, the study failed to consider company size in terms of revenue and their rankings in their respective industries in determining the final sample. The methodology used by the study was also limited to document review of corporate documents readily available to shareholders/investors that do not have special privilege in accessing corporate filings. Moreover, the questionnaire used by the study in assessing the corporate governance frameworks of family controlled and non-family controlled companies was based on the material used by ICD in their 2009 Corporate Governance Scorecard for Publicly Listed Companies, which was also patterned after the OECD Principles of Corporate Governance published in 2004. As a baseline research concerning the level of minority shareholder protection prevalent in the country, further study is recommended that would consider bigger sample than that utilized by the previous study in order to further assess the difference between the levels of minority shareholder rights protection provided by family controlled and non-family controlled publicly listed companies. The study also recommends that further researches dwell on the conceptual relationship between the separation of ownership and control to minority shareholder protection as an important factor of corporate governance. It is also suggested that an in-depth analysis of the underlying causes of poor minority shareholder protection in the country must be done. There is also a need for academic studies that will look into the reasons why publicly listed family controlled companies had better protection of minority shareholder rights that non-family controlled companies in the Philippines. Moreover, it is also recommended for further researches to consider cross analysis of data where equity structure is not the only independent variable being considered but to include company size as well. Studies that consider the impacts of foreign investments to a company’s corporate governance framework are also worth pursuing. In addition, the use of proxy voting facilities and confidential voting procedures should likewise be promoted in the country. Furthermore, there is also a great need for credit rating agencies to be established in the country that can provide pressures to companies to adopt good corporate governance policies or else receive poor credit ratings thus lose investors’ support. Lastly, the above recommendations will not be successful if not adequately enforced. As such a way to reinforce this is to make law compliance not only beneficially but rewarding as well. A way through this is by giving awards and citations to leading companies in terms of corporate governance. Such practice does not only recognize law-compliant companies but also help companies in assessing their performance and corporate governance practice, as against the best practices in the industry. Thus, it moves away from mere compliance to performance.